(untitled) (Revista Lusófona de Educação, 2026)
This article critically analyses the value attributed to university extension[1] in Angola, seeking to understand whether it is effectively realised as a vector of educational and social transformation or whether it remains an institutional promise that has not been fully fulfilled. The study adopts a mixed-methods approach, combining quantitative and qualitative data obtained through questionnaires administered to teachers and students, as well as interviews conducted with managers of higher education institutions. The findings reveal that, although extension activities are recognised as a strategic pillar of the university mission, significant weaknesses persist in terms of institutionalisation, funding, and articulation with teaching and research. It is concluded that university extension can assume a genuinely transformative role when supported by consistent institutional policies and sustained by the active involvement of the academic and social community.